2015
DOI: 10.1108/jfm-09-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the application of the Safe Working Cycle (SWC)

Abstract: Purpose-This paper aims to investigate the effectiveness of the Safe Working Cycle (SWC) in improving existing site safety performance of construction projects in Hong Kong, and to identify the perceived benefits, potential difficulties and insightful recommendations of implementing the SWC in the future. Design/methodology/approach-The professional views on the effectiveness of implementing the SWC, the benefits and difficulties of the SWC, together with the effective recommendations for future execution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 41 publications
(39 reference statements)
5
46
0
Order By: Relevance
“…There is no explicit or firm rule on how to choose and how many experts to choose for the Delphi process. The number of the responders, indeed, depends on the factors of homogeneous and heterogeneous types of the sample, target of the Delphi, duration of data gathering, domain of the problem and acceptability of the answer (Chan et al , 2007, 2010; Chan and Choi, 2015). The number of participants is usually less than 50 and most of the time is around 15 to 20 (Sarvari et al , 2019b).…”
Section: Methodsmentioning
confidence: 99%
“…There is no explicit or firm rule on how to choose and how many experts to choose for the Delphi process. The number of the responders, indeed, depends on the factors of homogeneous and heterogeneous types of the sample, target of the Delphi, duration of data gathering, domain of the problem and acceptability of the answer (Chan et al , 2007, 2010; Chan and Choi, 2015). The number of participants is usually less than 50 and most of the time is around 15 to 20 (Sarvari et al , 2019b).…”
Section: Methodsmentioning
confidence: 99%
“…Research results revealed that there was a miraculous decline in construction accidents rate immediately after the adaptation of SMS in Hong Kong. However, the decreasing accident rate has slackened recently [25][26][27]. Therefore, it is necessary to evaluate accident types which cause more fatalities in the Hong Kong construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these indifferent workers stated that the noise was not an issue and/or they were not bothered by it. With such a large proportion of exposed workers being aloof, this presents a significant barrier with respect to implementing hearing conservation efforts as disenchanted workers can negatively affect the success of occupational health and safety initiatives [ 22 , 23 ]. These results also support the assertion that workers do not fully comprehend the risk that they are exposed to [ 24 ] and that workers are becoming “normalized” to the excessive noise levels [ 25 ].…”
Section: Discussionmentioning
confidence: 99%